Percutaneous absorption of Carfentanil in vitro. (April 2021) - Dalton, Christopher; Watkins, Rachel; Pritchard, Sarah; Graham, Stuart
Abstract: Carfentanil is a synthetic opioid restricted to veterinary use due to its potency. Public health concerns have been raised as to the potential of carfentanil to exhibit toxicity after absorption via the percutaneous route following unintentional contamination. The current study measured the penetration of free base carfentanil through human, pig and rat skin using in vitro static diffusion cells. The human penetration rates were compared against literature toxicology values and indicated that, dependent on the contamination density, contamination area and residence time, skin decontamination and medical countermeasures may be required to ameliorate toxicity. The pig and rat skin penetration data will form the basis of future work to develop relevant in silico and in vivo models to further elucidate likely toxic effects and the medical strategies to mitigate against them. Highlights: Rat skin was more permeable to free base carfentanil than pig or human skin. Transient exposure to low contamination densities unlikely to lead to toxicity. There is the potential for prolonged penetration of carfentanil via the dermal route. Effective mitigation strategies may be required for high dose, long residence times.